Gamification: Meningkatkan Motivasi Belajar Siswa Di Sekolah Dasar - Jingga Pramesti Pujianingsih; Khusnul Khotimah; Rahma Putri Wibowot; Seillamitha Octaviona Lorenza (Lembaga Pengembangan Kinerja Dosen, 2024)
Gamification system-based learning is a learning method that uses game elements and game thinking in a non-game environment to improve student behavior and engagement in the learning process. The concept of gamification in learning minimizes lectures by teachers about the material, and emphasizes interactivity and student involvement in learning. This research uses the literature review method to comprehensively analyze articles published from 2020 to 2023, of course with several specifications determined and 4 articles selected. The results of this research state that the gamification method is very effective and appropriate for increasing student learning motivation, because in implementing gamification students are required to be active during the learning process and also present interactive material.